Music teacher education in Ireland and United Kingdom - Herrera Torres, Lucía; Lorenzo Quiles, Oswaldo; Ocaña Fernández, Almudena (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
In the frame of the international project ALPHA II-0448-A (Evaluation of Music Teacher Education Programmes), this paper makes a content analysis of all the music teacher education programmes of Ireland and United Kingdom. This review was made with emphasis on the educational dimension of the musical training given by the institutions of these two countries. Programme analysis denotes a clear parallelism between music teacher education in Ireland and the UK. It was also found a big disparity in undergraduate and graduate degrees among the programmes studied.